Exploration of Students' Skills in Describing Physics Problems: The Effect of STEM-Project-Based Learning - Nehru, Nehru; Kurniawan, Wawan; Riantoni, Cicyn (Indonesian Journal of Science and Mathematics Education, 2023)
The difficulty students face in describing problems from posed physics-related questions is an indicator that is rarely studied. This research explores students' abilities in describing electrical circuit problems based on implementing STEM-Project Based Learning (STEM-PBL). This study employed a mixed-methods approach with an explanatory model. The subjects were 35 undergraduate Physics Education students at the University of Jambi enrolled in the Electromagnetism course. Data collection was carried out through tests and interviews. The test instrument used five reasoned multiple-choice questions, while the interview instrument used open-ended questions based on the problems identified from the test results. The study's findings revealed an effect size of 2.1 (medium category) and an N-Gain of 0.5 (medium category). Thus, STEM-PBL influences students' ability to describe problems. Future research should investigate the influence of other variables, such as educational background and learning motivation, on the effectiveness of STEM-PBL in developing students' problem-description skills further.